El sector energético de AMLO: soberanía nacional y modelo de desarrollo endógeno (2018-2024) - Rousseau Chaigneau, Isabelle Marie (El Colegio de México A.C., 2025)
This article analyzes the decisions and measures of the administration of Andrés Manuel López Obrador (AMLO) in the energy sector between 2018 and 2024, within the framework of his political project known as the “Fourth Transformation” (4T). These policies sought to place the state–and its enterprises–at the center of Mexico’s energy system and to promote an endogenous development model aimed at restoring energy sovereignty. Within this context, the article addresses three questions: (1) What specific mechanisms and institutional instruments did the 4T employ to implement such a model? (2) To what extent do these tools align with prevailing understandings of “endogenous development”? (3) How successful was this approach in advancing toward greater energy sovereignty? The article offers an assessment of the achievements, shortcomings, and missteps of the administration’s energy policy, based on its stated objectives. It concludes by briefly identifying the multiple challenges this policy leaves to the next administration.